2022
DOI: 10.1038/s41598-022-21736-w
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and its correlation with handgrip strength in active community-dwelling older adults

Abstract: In this cross-sectional study, we assessed the physical fitness levels of active community-dwelling older adults. Moreover, we investigated the correlation of their (stratified by age and sex) fitness levels with handgrip strength (HGS). Comprehensive physical fitness tests, including sarcopenia screening, were conducted with a total of 2,130 older adults residing in a rural area of Taiwan. The 5th, 10th, 25th, 50th, 75th, 90th, and 95th percentiles of age- and sex-specific physical fitness levels were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Sousa et al [77] showed that combining aerobic training and strength training was more effective in improving 6-MWT performance than aerobic training performed alone in older men. The handgrip test is the most used muscle strength tool in clinical and scientific settings [78], standing out as an important health indicator in older people [79]. In agreement with a previous study involving the MTP [80], our results showed that this training form was effective in improving general muscle strength measured by the handgrip test in older people.…”
Section: Discussionsupporting
confidence: 89%
“…Sousa et al [77] showed that combining aerobic training and strength training was more effective in improving 6-MWT performance than aerobic training performed alone in older men. The handgrip test is the most used muscle strength tool in clinical and scientific settings [78], standing out as an important health indicator in older people [79]. In agreement with a previous study involving the MTP [80], our results showed that this training form was effective in improving general muscle strength measured by the handgrip test in older people.…”
Section: Discussionsupporting
confidence: 89%
“…The moderate to strong positive correlations found between physical conditioning variables, in particular handgrip strength, in bilateral and unilateral tasks in linear and nonlinear variables, could be used as a first observation of balance status. These preliminary findings can also add on benefits for physical activity and targeted training in this population, which could also benefit functionality [ 48 , 49 ]. Muscle strength helps stabilize posture, and HGS correlations also highlight the vital role of muscle capacity in posture regulation for adults with achondroplasia.…”
Section: Discussionmentioning
confidence: 99%
“…While these assessments are commonly used to evaluate different aspects of physical fitness, our findings suggest that the association between Hand-Grip strength and Sit and Sit-andreach flexibility in this adolescent population is remarkably weak. The Pearson correlation coefficient of approximately 0.084 indicates a negligible positive correlation between the two variables (Pan, et al 2022).…”
Section: Discussionmentioning
confidence: 99%